(untitled) (Bangladesh Journal of Medical Science, 2018)
Background: This study was aimed to find out the central and peripheral analgesic activity of hydro methanolic extract of aerial parts of Onosma bracteatum. Material and methods: The central and peripheral analgesic activity is evaluated by tail flick test and acetic acid induced writhing test at the doses of 50, 100, 250 and 500mg/kg body weight respectively in animal models. Results: The results obtained from Tail flick test revealed that O. bracteatum possesses potent analgesic effects by inducing significant increase in latency period in dose dependent manner at all doses at 1, 2 and 3 hours post feeding respectively. The maximum effect was observed at a dose of 500mg/kg i.e. 258.9% (p<0.05) at 3hrs post feeding. Diclofenac sodium (5mg/kg body weight) run as standard also increased the latency period continuously and highest activity was noted at 3hr i.e. 284.5% (p<0.05). Acetic acid induced writhing test also showed significant activity in a similar manner by O. bracteatum i.e 54% (p<0.05) at 500mg/kg while standard drug Diclofenic sodium (5mg/kg body weight) showed 45.9% (p<0.05) activity. Conclusion: It is concluded that O. bracteatum possesses significant central and peripheral analgesic activity in animal model. Bangladesh Journal of Medical Science Vol.17(1) 2018 p.36-41